Production method of ultrathin copper foil with high tensile strength and high elongation

By optimizing the additive ratio and electroplating conditions of electrolytic copper foil, using the synergistic effects of chloride ions, leveling agents, inhibitors, brighteners and sulfur-containing additives, the problem of difficult to produce ultra-thin, high tensile, and high-extended copper foil with superior performance in the prior art is solved, and the high-performance production of copper foil is achieved.

CN119506986APending Publication Date: 2025-02-25TIANJIN POLYTECHNIC UNIV +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510030673.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art lacks excellent additive ratios, making it difficult to produce ultra-thin, high tensile, and high extension copper foil with superior performance.

Method used

By optimizing the additive ratio, including the synergistic effect of chloride ions, leveling agents, inhibitors, brighteners and sulfur-containing additives, the composition and electroplating conditions of the electrolyte are adjusted to prepare ultra-thin copper foil with high tensile strength and elongation.

Benefits of technology

The copper foil is produced with thin thickness, high tensile strength, high elongation and bright surface, meeting the high requirements of lithium batteries for copper foil performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506986A_ABST
    Figure CN119506986A_ABST
Patent Text Reader

Abstract

The invention discloses a production method of an ultrathin copper foil with high tensile strength and high elongation, which applies a synergistic effect of chloride ions, a leveling agent, an inhibitor, a brightener and a sulfur-containing additive, so that crystal grains are more compact, and the copper foil is smoother, brighter, finer and more uniform in SEM (scanning electron microscope) observation. And data measured by a tension test can show that the tensile strength and the ductility are remarkably improved through the synergistic effect of several additives. The thickness of the copper foil prepared by the production method disclosed by the invention is 4 # imgabs 0 # and 12 # imgabs 1 # m, the rough surface roughness Ra is (0.04-0.46) # imgabs 2 # m, the Rz is (0.66 # imgabs 3 # 1.63) # imgabs 4 # m, and the tensile strength is 650 # imgabs 5 # 950 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolytic copper foil, and in particular relates to a production method of an ultra-thin high-tensile-resistance and high-elongation copper foil. Background Art

[0002] As the world enters the information age at an accelerated pace and new energy vehicles develop rapidly, the performance requirements and market demand for lithium batteries are increasing. Copper foil, as an indispensable member of lithium batteries, has made an indelible contribution.

[0003] The lithium batteries now in demand require a smaller size and a larger capacity, so the thickness of the copper foil required is getting thinner and thinner. Copper foil is mainly used in lithium batteries, mainly in the manufacture of the negative electrode of lithium batteries. Lithium batteries are mainly used in new energy electric vehicle batteries, aerospace, energy storage systems, mobile phones and computers. Copper foil has the characteristics of strong conductivity, soft texture, relatively mature manufacturing process, high cost performance and relatively low price. The conductivity of metal copper is lower, so the resistance is lower, so as to form a larger current output and cause less current loss. Therefore, copper foil has become the first choice for the negative electrode current collector of lithium electronic batteries. As lithium batteries develop towards small size and large capacity, copper foil is also developing towards lightness and thinness, and there are higher requirements for the performance of copper foil, such as thinner thickness, greater tensile strength and elongation.

[0004] There are two processes for producing copper foil: one is mechanical forging, which presses copper sheets into copper foil; the other is to produce copper foil according to the electrolytic method. Although the performance of mechanically forged copper foil is also relatively excellent, due to the relatively complex mechanical forging process and high production cost, mechanical forging is not used as the main production process.

[0005] In order to reduce costs and simplify the production process, electrolytic copper foil has become the main process. However, electrolytic copper foil production requires a large number of experiments to find the optimal additive ratio in order to obtain copper foil with better performance. According to a large number of experiments, the finer the copper foil grains, the more orderly the arrangement between the grains, and the greater the tensile strength. Summary of the invention

[0006] In view of the problem that the prior art lacks excellent additive ratios to produce copper foil with superior performance, the present invention provides a method for producing ultra-thin high tensile strength and high elongation copper foil. The purpose of the present invention is to propose a method for producing high tensile strength and high elongation copper foil, and to produce copper foil with better performance by optimizing the additive ratio to solve the problems in practical application. It is a method for producing ultra-thin copper foil with thin thickness, high tensile strength, high elongation and bright surface. In order to solve the difficulties encountered in production, the present invention obtains copper foil with fine and uniform grains and excellent mechanical properties by testing the synergistic effect of a large number of combined additives to meet the development trend of lithium battery copper foil towards lightness and thinness. The present invention prepares copper foil by electroplating according to the principle of electrolytic cell, and adds appropriate additives to improve the performance of copper foil, and explores the performance of copper foil through structural testing.

[0007] The purpose of the present invention is achieved through the following technical solutions: A method for producing an ultra-thin high-tensile-resistance and high-elongation copper foil comprises the following steps: (1) Distilled water, copper sulfate pentahydrate, and concentrated sulfuric acid are used to prepare a basic electrolyte, wherein the basic electrolyte contains Cu 2+ Concentration is 80 85 g / L, H2SO4 concentration is 111 130 g / L; Pour the electrolyte into the electrolytic cell and heat it to the working temperature 40 65℃; (2) adding chloride ions, leveling agents, brighteners, inhibitors, and sulfur-containing additives into the electrolytic cell; The chloride ion is hydrochloric acid or hydrochloride, and the chloride ion concentration is 28 34 mg / L; The leveling agent is one or more of gelatin, collagen or quaternary ammonium salt compounds containing conjugated bonds, and its concentration is 8 25 mg / L, any ratio when mixed; The brightener is one or more of ethylene thiourea, sodium 3-mercapto-1-propane sulfonate, and sodium polydisulfide propane sulfonate, with a concentration of 3.0 13 mg / L, any ratio when mixed; The inhibitor is one or more of polyethylene glycol, polypropylene glycol, and polyoxyethylene ether, with a concentration of 2.0 23 mg / L, any ratio when mixed; The sulfur-containing additive is one or more of sodium thiazoline dithiopropane sulfonate, 4-phenylimidazole, tetrahydrothiazolidinethione, 5-methylthiazole and 2-mercaptobenzimidazole, with a concentration of 0.5 21 mg / L, any ratio when mixed; (3) Turn on the DC power supply and set the current density to 30 60 A / dm 2 , power-on time is 200 500 s; (4) After electroplating, remove the cathode plate, rinse it with a large amount of distilled water, and then immerse it in the passivation solution for 5 minutes. 300s, take it out and rinse it again with a large amount of distilled water to rinse out the residual solution and passivation solution and then dry it; (5) After drying, the copper foil is peeled off from the cathode plate to obtain a bright copper foil. The ultra-thin high tensile strength and high elongation copper foil has the following performance parameters: Copper foil thickness is 4μm 12μm, elongation 10.60% 19.80%, roughness Ra of matte surface is 0.04μm 0.46μm, Rz is 0.66μm 1.63μm, tensile strength 650 MPa 950 MPa.

[0008] In the present invention: Furthermore, the chloride ions in step (2) are preferably provided by hydrochloric acid, and the preferred hydrochloride is sodium chloride or potassium chloride.

[0009] Furthermore, in step (3), the DC power supply is turned on, and the current density is preferably set to 35 A / dm 2 , the power-on time is 300s.

[0010] Furthermore, the passivation solution described in step (4) is obtained by stirring and evenly mixing 21.0 g of citric acid, 2 mL of phytic acid mother liquor, 0.5 g of sodium tungstate, 0.1 g of benzotriazole and 1.0 mL of lactic acid, adding them to 100 mL of distilled water to dissolve, and adjusting the pH value to make it acidic.

[0011] In step (2), the additives used in the present invention use organic sulfide and nitrogen-containing organic matter as brighteners. Two or more brighteners are synergistically matched at a certain concentration ratio. The inventors found through comparative experiments that although the apparent characteristics presented by adding only organic sulfide or only nitrogen-containing organic matter are relatively excellent, the effect is not as ideal as the synergistic effect of adding organic sulfide and nitrogen-containing organic matter as brighteners. The working principle of the brightener is to form a molecular layer on the substrate, so that the copper grains have no orientation preference, and have a certain grain refinement effect, making the grains finer and the arrangement between the grains more flat, so that the roughness of the copper foil can be reduced within a certain concentration, and the tensile strength and elongation of the copper foil can be improved.

[0012] The sulfur-containing additive used in the present invention can be selected from conventional brighteners of the same type. The inventors have found in their research that the brighteners containing sulfur heterocyclic structures include sodium thiazoline dithiopropane sulfonate, 4-phenylimidazole, tetrahydrothiazolidinethione, 5-methylthiazole and 2-mercaptobenzimidazole. The synergistic effect of the sulfur-containing additive combined with the polyol inhibitor is ideal. According to comparative experiments, it can be seen that adding only the sulfur-containing additive or only the polyol inhibitor on the basis of the prior art cannot obtain a relatively ideal copper foil. On the basis of the prior art, only the sulfur-containing additive is added, because the Cu in the electrolysis process 2+ It is not inhibited, so the plated coating is extremely rough, and the grains are larger, so the tensile strength is smaller, and the mechanical properties do not meet the ideal requirements; on the basis of the existing technology, only inhibitors are added. Due to the lack of sulfur-containing additives, although the coating is inhibited, the brightness is poor and the roughness is even less ideal. Therefore, to obtain an ideal sample, the above-mentioned additives must work synergistically, and none of them can be missing. Only in this way can the electrolytic sample meet the production requirements and further improve the tensile strength of the copper foil. The tensile strength measured by the test results >650MPa, and effectively improves its elongation.

[0013] Chloride ions are currently an indispensable additive in the production of copper foil. The inventors found in their research that the above-mentioned chloride ions generally come from hydrochloric acid or hydrochloride. The preferred hydrochloride is sodium chloride or potassium chloride. Hydrochloric acid is preferably used to provide chloride ions. Chloride ions generally have four functions: (1) Inhibition due to Cu + With Cl - Combined with CuCl insoluble matter, CuCl is adsorbed on the cathode plate surface to inhibit Cu 2 + Reduction, thus making the coating finer, smoother and denser; (2) Acceleration, which is generally reflected in the formation of bridges between chloride ions and brighteners, thereby accelerating the transmission efficiency of substances and making Cu 2+ The reduction rate is accelerated; (3) Catalytic effect, reflected in Cl - Cu 2+ Reduction to Cu + , thereby increasing the reduction rate; (4) Stress reliever: Chloride ions can help the anode dissolve, and work synergistically with brightener and leveling agent to make the coating brighter and smoother.

[0014] The present invention also relates to an ultra-thin high tensile strength and high elongation copper foil, which is obtained by using the above-mentioned production method of the ultra-thin high tensile strength and high elongation copper foil. The prepared ultra-thin high tensile strength and high elongation copper foil has the following performance parameters: Copper foil thickness is 4μm 12μm, elongation 10.60% 19.80%, roughness Ra of matte surface is 0.04μm 0.46μm, Rz is 0.66μm 1.63μm, tensile strength 650 MPa 950 MPa.

[0015] Compared with the prior art, the present invention has the following advantages: The present invention discloses a method for producing ultra-thin high tensile strength and high elongation copper foil. The present invention utilizes the synergistic effect of chloride ions, leveling agents, inhibitors, brighteners, and sulfur-containing additives to make the grains denser, and the SEM observation is smoother, brighter, finer, and more uniform. The data obtained through the tensile test show that the synergistic effect of several additives significantly improves the tensile strength and elongation. The copper foil produced by the production method of the present invention has a thickness of 4 12 m, elongation is 10.60% 19.80%, the roughness of the rough surface Ra is (0.04 0.46) m, Rz is (0.66 1.63) m, tensile strength is 650 950MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.

[0017] Figure 1 This is a SEM image of the copper foil prepared by the method for producing an ultra-thin high tensile strength and high elongation copper foil according to Example 3 of the present invention, magnified 1000 times; Figure 2 This is a SEM image of the copper foil prepared in Comparative Example 2 of the present invention, magnified 1000 times; Figure 3 This is a SEM image of the copper foil prepared in Comparative Example 4 of the present invention, magnified 1000 times; Figure 4 This is an X-ray diffraction pattern of a copper foil prepared by a method for producing an ultra-thin high tensile strength and high elongation copper foil according to Example 3 of the present invention; Figure 5 This is the X-ray diffraction pattern of the copper foil prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to more clearly and completely describe the technology and principles in the present invention. Obviously, the embodiments are only a part of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0019] Embodiment 1: A method for producing an ultra-thin high-tensile-resistance and high-elongation copper foil comprises the following steps: (1) Weigh copper sulfate pentahydrate and concentrated sulfuric acid to prepare copper sulfate base solution; 2+ The concentration is 80g / L, H2SO4 is 120g / L, pour the copper sulfate base solution into the electrolytic cell, and control the temperature of the electrolyte at 40 65℃; (2) Chloride ions, inhibitors, levelers, brighteners and sulfur-containing additives are added to the electrolytic cell. The components and concentrations of the combined additives are: 32 mg / L chloride ions, 8 mg / L gelatin, 3 mg / L sodium polydisulfide propane sulfonate, 4 mg / L polyethylene glycol, 5 mg / L sodium thiazoline disulfide propane sulfonate, and 0.5 mg / L tetrahydrothiazolidinethione. The additives in trace amounts in the electrolyte are mixed uniformly by blowing in air. (3) Connect the positive and negative electrodes of the DC power supply to the electrolytic cell and power it on. The current density is set to 35A / dm 2 , the power-on time is 300s, and the air flow is ensured to be smooth during power-on. After the power-on is over, the cathode plate is immediately taken out and rinsed with a large amount of distilled water. After rinsing the residual electrolyte, it is immersed in the passivation solution. After soaking for 15s, it is rinsed again with distilled water, and the residual passivation solution is rinsed and dried. (4) After drying, the copper foil is peeled off from the cathode plate to obtain a bright, high-tensile and high-elongation ultra-thin copper foil; The peeled copper foil was cut into a rectangle of 1.5×3.0 mm, placed on a stage, and the crystallographic properties were observed by an X-ray diffractometer.

[0020] The results show that: The thickness of the copper foil is 7.6 m, roughness of the rough surface Ra=0.46 m,Rz=1.63 m, and the tensile strength is 687.144 MPa.

[0021] Embodiment 2: A method for producing an ultra-thin high-tensile-resistance and high-elongation copper foil comprises the following steps: (1) Weigh copper sulfate pentahydrate and concentrated sulfuric acid to prepare copper sulfate base solution; 2+The concentration is 82g / L, H2SO4 is 119g / L, pour the copper sulfate base solution into the electrolytic cell, and control the temperature of the electrolyte at 40 65℃; (2) Chloride ions, inhibitors, levelers, brighteners and sulfur-containing additives are added to the electrolytic cell. The components and concentrations of the combined additives are: 34 mg / L chloride ions, 8 mg / L collagen, 3 mg / L ethylene thiourea, 5 mg / L polypropylene glycol, 3 mg / L polyoxyethylene ether, 10 mg / L sodium thiazolinyl dithiopropane sulfonate, 0.5 mg / L tetrahydrothiazolidinethione, and 1 mg / L 2-mercaptobenzimidazole. The additives in trace amounts in the electrolyte are mixed uniformly by blowing in air. (3) Connect the positive and negative electrodes of the DC power supply to the electrolytic cell and power it on. The current density is set to 35A / dm 2 , the power-on time is 300s, and the air flow is ensured to be smooth during power-on. After the power-on is over, the cathode plate is immediately taken out and rinsed with a large amount of distilled water. After rinsing the residual electrolyte, it is immersed in the passivation solution. After soaking for 15s, it is rinsed again with distilled water, and the residual passivation solution is rinsed and dried. (4) After drying, the copper foil is peeled off from the cathode plate to obtain a bright, high-tensile and high-elongation ultra-thin copper foil; The peeled copper foil was cut into a rectangle of 1.5×3.0 mm, placed on a stage, and the crystallographic properties were observed by an X-ray diffractometer.

[0022] The results show that: The thickness of the copper foil is 7.2 m, roughness of the rough surface Ra=0.2 m,Rz=1.18 m, and the tensile strength is 667.224MPa.

[0023] Embodiment 3: A method for producing an ultra-thin high-tensile-resistance and high-elongation copper foil comprises the following steps: (1) Weigh copper sulfate pentahydrate and concentrated sulfuric acid to prepare copper sulfate base solution; 2+ The concentration is 84g / L, H2SO4 is 115g / L, pour the copper sulfate base solution into the electrolytic cell, and control the temperature of the electrolyte at 40 65℃; (2) Chloride ions, inhibitors, levelers, brighteners and sulfur-containing additives are added to the electrolytic cell. The components and concentrations of the combined additives are: 31 mg / L chloride ions, 10 mg / L gelatin, 8 mg / L collagen, 3 mg / L ethylenethiourea, 4 mg / L sodium 3-mercapto-1-propane sulfonate, 5 mg / L sodium polydisulfide propane sulfonate, 4 mg / L polyethylene glycol, 6 mg / L polypropylene glycol, 10 mg / L sodium thiazoline disulfide propane sulfonate, 1 mg / L 4-phenylimidazole, 1 mg / L tetrahydrothiazolidinethione, and 2 mg / L 5-methylthiazole. The additives in trace amounts in the electrolyte are mixed uniformly by blowing in air. (3) Connect the positive and negative electrodes of the DC power supply to the electrolytic cell and power it on. The current density is set to 35A / dm 2 , the power-on time is 300s, and the air flow is ensured to be smooth during power-on. After the power-on is over, the cathode plate is immediately taken out and rinsed with a large amount of distilled water. After rinsing the residual electrolyte, it is immersed in the passivation solution. After soaking for 15s, it is rinsed again with distilled water, and the residual passivation solution is rinsed and dried. (4) After drying, the copper foil is peeled off from the cathode plate to obtain a bright, high-tensile and high-elongation ultra-thin copper foil; The peeled copper foil was cut into a rectangle of 1.5×3.0 mm, placed on a stage, and the crystallographic properties were observed by an X-ray diffractometer.

[0024] The results show that: The thickness of the copper foil is 7.3 m, roughness of the rough surface Ra=0.04 m,Rz=0.66 m, and the tensile strength is 783.912 MPa.

[0025] pass Figure 4 It can be seen that the coating of Example 3 is better than that of Comparative Example 2. Figure 2 , Comparative Example 4 Figure 3 , the grains shown in Example 3 are finer, and the coating is smoother and denser; Figure 4 , Figure 5 It can be seen that the 220 crystal plane diffraction peak intensity that determines the tensile strength in Example 3 is significantly stronger than that in the comparative example; this is also the reason why the mechanical properties and appearance characteristics of the copper foil prepared in Example 3 are superior to those in the comparative example. Embodiment 4: A method for producing an ultra-thin high-tensile-resistance and high-elongation copper foil comprises the following steps: (1) Weigh copper sulfate pentahydrate and concentrated sulfuric acid to prepare copper sulfate base solution; 2+The concentration is 85g / L, H2SO4 is 120g / L, pour the copper sulfate base solution into the electrolytic cell, and control the temperature of the electrolyte at 40 65℃; (2) Chloride ions, inhibitors, levelers, brighteners and sulfur-containing additives are added to the electrolytic cell. The components and concentrations of the combined additives are: 28 mg / L chloride ions, 10 mg / L gelatin, 7 mg / L collagen, 8 mg / L quaternary ammonium salt compounds containing conjugated bonds, 3 mg / L ethylenethiourea, 3 mg / L sodium polydisulfide dipropane sulfonate, 6 mg / L polyethylene glycol, 1 mg / L 4-phenylimidazole, 1 mg / L tetrahydrothiazolidinethione, and 1 mg / L 5-methylthiazole. The additives in trace amounts in the electrolyte are mixed uniformly by blowing in air. (3) Connect the positive and negative electrodes of the DC power supply to the electrolytic cell and power it on. The current density is set to 35A / dm 2 , the power-on time is 300s, and the air flow is ensured to be smooth during power-on. After the power-on is over, the cathode plate is immediately taken out and rinsed with a large amount of distilled water. After rinsing the residual electrolyte, it is immersed in the passivation solution. After soaking for 15s, it is rinsed again with distilled water, and the residual passivation solution is rinsed and dried. (4) After drying, the copper foil is peeled off from the cathode plate to obtain a bright, high-tensile and high-elongation ultra-thin copper foil; The peeled copper foil was cut into a rectangle of 1.5×3.0 mm, placed on a stage, and the crystallographic properties were observed by an X-ray diffractometer.

[0026] The results show that: The thickness of the copper foil is 7.3 m, roughness of the rough surface Ra=0.3 m,Rz=1.52 m, and the tensile strength is 942.652MPa.

[0027] Embodiment 5: A method for producing an ultra-thin high-tensile-resistance and high-elongation copper foil comprises the following steps: (1) Weigh copper sulfate pentahydrate and concentrated sulfuric acid to prepare copper sulfate base solution; 2+ The concentration is 81g / L, H2SO4 is 130g / L, pour the copper sulfate base solution into the electrolytic cell, and control the temperature of the electrolyte at 40 65℃; (2) Chloride ions, inhibitors, levelers, brighteners and sulfur-containing additives are added to the electrolytic cell. The components and concentrations of the combined additives are: 30 mg / L chloride ions, 10 mg / L gelatin, 6 mg / L collagen, 9 mg / L quaternary ammonium salt compounds containing conjugated bonds, 4 mg / L sodium 3-mercapto-1-propane sulfonate, 8 mg / L polyethylene glycol, 5 mg / L polypropylene glycol, 10 mg / L polyoxyethylene ether, 13 mg / L sodium thiazolinyl dithiopropane sulfonate, 1 mg / L 4-phenylimidazole, 1 mg / L tetrahydrothiazolidinethione, 2 mg / L 5-methylthiazole, and 2 mg / L 2-mercaptobenzimidazole. The additives in trace amounts in the electrolyte are mixed uniformly by blowing in air. (3) Connect the positive and negative electrodes of the DC power supply to the electrolytic cell and power it on. The current density is set to 35A / dm 2 , the power-on time is 300s, and the air flow is ensured to be smooth during power-on. After the power-on is over, the cathode plate is immediately taken out and rinsed with a large amount of distilled water. After rinsing the residual electrolyte, it is immersed in the passivation solution. After soaking for 15s, it is rinsed again with distilled water, and the residual passivation solution is rinsed and dried. (4) After drying, the copper foil is peeled off from the cathode plate to obtain a bright, high-tensile and high-elongation ultra-thin copper foil; The peeled copper foil was cut into a rectangle of 1.5×3.0 mm, placed on a stage, and the crystallographic properties were observed by an X-ray diffractometer.

[0028] The results show that: The thickness of the copper foil is 7.7 m, roughness of the rough surface Ra=0.32 m,Rz=1.11 m, and the tensile strength is 756.296 MPa.

[0029] Comparative Example 1: The production method of copper foil comprises the following steps: (1) Weigh copper sulfate pentahydrate and concentrated sulfuric acid to prepare copper sulfate base solution; 2+ The concentration is 83g / L, H2SO4 is 128g / L, pour the copper sulfate base solution into the electrolytic cell, and control the temperature of the electrolyte at 40 65℃; (2) Chloride ions, inhibitors, levelers, brighteners and sulfur-containing additives are added to the electrolytic cell. The components and concentrations of the combined additives are: 28 mg / L chloride ions, 9 mg / L gelatin, 8 mg / L collagen, 5 mg / L sodium 3-mercapto-1-propane sulfonate, 5 mg / L sodium polydisulfide propane sulfonate, and 10 mg / L polyethylene glycol. The additives in trace amounts in the electrolyte are mixed uniformly by blowing in air. (3) Connect the positive and negative electrodes of the DC power supply to the electrolytic cell and power it on. The current density is set to 35A / dm 2 , the power-on time is 300s, and the air flow is ensured to be smooth during power-on. After the power-on is over, the cathode plate is immediately taken out and rinsed with a large amount of distilled water. After rinsing the residual electrolyte, it is immersed in the passivation solution. After soaking for 15s, it is rinsed again with distilled water, and the residual passivation solution is rinsed and dried. (4) After drying, the copper foil is peeled off from the cathode plate to obtain a bright, high-tensile and high-elongation ultra-thin copper foil; The peeled copper foil was cut into 1.5×3.0 mm rectangles, placed on the stage, and the crystallographic properties were observed by X-ray diffractometer; The thickness of the copper foil is 7.1 m, roughness of the rough surface Ra = 1.61 m, Rz=9.5 m, and the tensile strength is 350.243 MPa.

[0030] The results show that: Although the apparent characteristics presented by adding only organic sulfide or only nitrogen-containing organic matter are relatively excellent, the effect is not as ideal as the synergistic effect of adding organic sulfide and nitrogen-containing organic matter as brighteners.

[0031] Comparative Example 2: The production method of copper foil comprises the following steps: (1) Weigh copper sulfate pentahydrate and concentrated sulfuric acid to prepare copper sulfate base solution; 2+ The concentration is 81g / L, H2SO4 is 120g / L, pour the copper sulfate base solution into the electrolytic cell, and control the temperature of the electrolyte at 40 65℃; (2) Chloride ions, inhibitors, levelers, brighteners and sulfur-containing additives are added to the electrolytic cell. The components and concentrations of the combined additives are: 31 mg / L chloride ions, 8 mg / L gelatin, 10 mg / L collagen, 3 mg / L ethylene thiourea, and 8 mg / L polyethylene glycol. The additives in trace amounts in the electrolyte are mixed uniformly by blowing in air. (3) Connect the positive and negative electrodes of the DC power supply to the electrolytic cell and power it on. The current density is set to 35A / dm 2 , the power-on time is 300s, and the air flow is ensured to be smooth during power-on. After the power-on is over, the cathode plate is immediately taken out and rinsed with a large amount of distilled water. After rinsing the residual electrolyte, it is immersed in the passivation solution. After soaking for 15s, it is rinsed again with distilled water, and the residual passivation solution is rinsed and dried. (4) After drying, the copper foil is peeled off from the cathode plate to obtain a bright, high-tensile and high-elongation ultra-thin copper foil; The peeled copper foil was cut into 1.5×3.0 mm rectangles, placed on the stage, and the crystallographic properties were observed by X-ray diffractometer; The thickness of the copper foil is 7.7 m, roughness of the rough surface Ra=1.92 m,Rz=10.66 m, and the tensile strength is 371.912MPa.

[0032] The results show that: pass Figure 2 The SEM image of the copper foil prepared by the production method of the copper foil of Comparative Example 2 is magnified 1000 times; it shows that although the appearance characteristics presented by adding only organic sulfide or only nitrogen-containing organic matter are relatively excellent, the effect is not as ideal as the synergistic effect of adding organic sulfide and nitrogen-containing organic matter as brighteners.

[0033] Comparative Example 3: The production method of copper foil comprises the following steps: (1) Weigh copper sulfate pentahydrate and concentrated sulfuric acid to prepare copper sulfate base solution; 2+ The concentration is 83g / L, H2SO4 is 111g / L, pour the copper sulfate base solution into the electrolytic cell, and control the temperature of the electrolyte at 40 65℃; (2) Chloride ions, inhibitors, levelers, brighteners and sulfur-containing additives are added to the electrolytic cell. The components and concentrations of the combined additives are: 34 mg / L chloride ions, 9 mg / L gelatin, 9 mg / L collagen, 3 mg / L ethylene thiourea, 3 mg / L sodium 3-mercapto-1-propane sulfonate, 4 mg / L sodium polydisulfide propane sulfonate, 4 mg / L polyethylene glycol, 2 mg / L polypropylene glycol, and 10 mg / L polyoxyethylene ether. The additives in trace amounts in the electrolyte are mixed uniformly by blowing in air. (3) Connect the positive and negative electrodes of the DC power supply to the electrolytic cell and power it on. The current density is set to 35A / dm 2 , the power-on time is 300s, and the air flow is ensured to be smooth during power-on. After the power-on is over, the cathode plate is immediately taken out and rinsed with a large amount of distilled water. After rinsing the residual electrolyte, it is immersed in the passivation solution. After soaking for 15s, it is rinsed again with distilled water, and the residual passivation solution is rinsed and dried. (4) After drying, the copper foil is peeled off from the cathode plate to obtain a bright, high-tensile and high-elongation ultra-thin copper foil; The peeled copper foil was cut into 1.5×3.0 mm rectangles, placed on the stage, and the crystallographic properties were observed by X-ray diffractometer; The thickness of the copper foil is 7.4 m, roughness of the rough surface Ra = 1.23 m,Rz=8.66 m, and the tensile strength is 351.159 MPa.

[0034] The results show that: On the basis of the existing technology, adding only sulfur-containing additives or only adding polyol inhibitors cannot obtain a more ideal copper foil. On the basis of the existing technology, only adding sulfur-containing additives, due to the electrolysis process of Cu 2+ It is not inhibited, so the plated coating is extremely rough, and the grains are larger, so the tensile strength is smaller, and the mechanical properties do not meet the ideal requirements; on the basis of the existing technology, only inhibitors are added. Due to the lack of sulfur-containing additives, although the coating is inhibited, the brightness is poor and the roughness is even worse. Therefore, in order to obtain an ideal sample, the above-mentioned additives must work synergistically, and none of them can be missing. Only in this way can the electrolyzed sample meet the production requirements.

[0035] Through Figure 5 The X-ray diffraction pattern of the copper foil prepared by the production method of the copper foil of Comparative Example 3 shows that the additive ratio of Comparative Example 3 is stronger than that of Example 3 through the relative strength of the diffraction peaks measured by X-ray diffraction. Figure 4 The third diffraction peak, i.e., the 220 peak, is lower. The growth of the crystal plane toward 220 is inhibited. Therefore, the tensile strength and elongation of the copper foil prepared by the additive added in Comparative Example 3 are also lower than those of the copper foil prepared by the additive added in Example 3.

[0036] Comparative Example 4: The production method of copper foil comprises the following steps: (1) Weigh copper sulfate pentahydrate and concentrated sulfuric acid to prepare copper sulfate base solution; 2+ The concentration is 81g / L, H2SO4 is 119g / L, pour the copper sulfate base solution into the electrolytic cell, and control the temperature of the electrolyte at 40 65℃; (2) Chloride ions, inhibitors, levelers, brighteners and sulfur-containing additives are added to the electrolytic cell. The components and concentrations of the combined additives are: 30 mg / L chloride ions, 10 mg / L gelatin, 9 mg / L collagen, 5 mg / L ethylenethiourea, 5 mg / L sodium 3-mercapto-1-propane sulfonate, 3 mg / L sodium polydisulfide propane sulfonate, 15 mg / L sodium thiazoline disulfide propane sulfonate, and 1 mg / L tetrahydrothiazolidinethione. The additives in trace amounts in the electrolyte are mixed uniformly by blowing in air. (3) Connect the positive and negative electrodes of the DC power supply to the electrolytic cell and power it on. The current density is set to 35A / dm 2, the power-on time is 300s, and the air flow is ensured to be smooth during power-on. After the power-on is over, the cathode plate is immediately taken out and rinsed with a large amount of distilled water. After rinsing the residual electrolyte, it is immersed in the passivation solution. After soaking for 15s, it is rinsed again with distilled water, and the residual passivation solution is rinsed and dried. (4) After drying, the copper foil is peeled off from the cathode plate to obtain a bright, high-tensile and high-elongation ultra-thin copper foil; The peeled copper foil was cut into 1.5×3.0 mm rectangles, placed on the stage, and the crystallographic properties were observed by X-ray diffractometer; The thickness of the copper foil is 7.2 m, roughness of the rough surface Ra=0.88 m,Rz=4.53 m, and the tensile strength is 398.672 MPa.

[0037] The results show that: Figure 3 The SEM image of the copper foil prepared by the production method of the copper foil of Comparative Example 4 is magnified 1000 times; it shows that adding only sulfur-containing additives or only adding polyol inhibitors on the basis of the existing technology cannot obtain a more ideal copper foil. On the basis of the existing technology, only adding sulfur-containing additives, due to the copper in the electrolysis process 2+ It is not inhibited, so the plated coating is extremely rough, and the grains are larger, so the tensile strength is smaller, and the mechanical properties do not meet the ideal requirements; on the basis of the existing technology, only inhibitors are added. Due to the lack of sulfur-containing additives, although the coating is inhibited, the brightness is poor and the roughness is even worse. Therefore, in order to obtain an ideal sample, the above-mentioned additives must work synergistically, and none of them can be missing. Only in this way can the electrolyzed sample meet the production requirements.

[0038] Results and Discussion: The copper foils prepared in Examples 1-5 and Comparative Examples 1-4 were cut into a size of 1×5 cm, and the tensile strength and elongation were tested using a tensile testing machine, and the roughness was measured using a roughness meter. The final measurement results are shown in the following table: Table 1: Performance parameters of copper foil obtained in Examples and Comparative Examples

[0039] It can be seen from the table summarized in the above embodiments and comparative examples that the copper foil thickness of the present invention is 4 12 m, elongation is 10.60% 19.80%, roughness Ra of matte surface is 0.04μm 0.46μm, Rz is 0.66μm 1.63μm, tensile strength 650 MPa 950 MPa. Compared with the comparative example, the embodiment has better mechanical properties and more ideal appearance characteristics. The surface roughness of the sample prepared in the embodiment is also smaller. Therefore, according to the method of this patent, a copper foil with superior performance and smoother surface can be prepared.

[0040] pass Figure 1 , Figure 2 , Figure 3 It can be seen from the SEM image that, according to the copper foil prepared in the above embodiment, the grains are finer and the coating is smoother in a microscopic state, while the copper foil prepared in the comparative example has too large grains and the coating is rougher and more uneven than that in the embodiment.

[0041] According to the literature, it is concluded that the diffraction peaks detected by XRD include 111 crystal plane, 200 crystal plane, 220 crystal plane and 311 crystal plane; among them, 220 crystal plane determines the tensile strength of copper foil. The higher the strength of 220 crystal plane, the more it promotes the growth of crystal plane in the 220 direction, so the tensile strength and elongation of copper foil are higher. This is also because the copper foil grains are finer and the coating is finer and smoother.

[0042] According to the embodiment, we have successfully prepared high tensile and high elongation copper foil in the laboratory based on the synergistic effect of various additives combined. The above-mentioned sulfur-containing additives are good grain refiners, levelers and brighteners, but before optimizing the optimal concentration ratio of the combined additives or adding them alone to the copper sulfate electrolyte, they cannot better exert their brightening effect, leveling effect and refinement effect. To exert the real effect, the optimal ratio of other combined additives must be optimized so as to exert synergistic effect with the combined additives.

[0043] This patent is to study how to adjust the amount of additives to obtain copper foil with better performance. It also uses organic additives that are more common in industrial production. Future research can replace it with other additives to optimize a more ideal concentration ratio and prepare copper foil with better performance. The research work in this article is all conducted in the laboratory. In future research, the optimal concentration ratio and its basic electrolyte obtained in this article can be used in the production line of the copper foil company, and its concentration ratio and parameters can be further optimized in actual production.

[0044] In the production process of copper foil, anti-oxidation is particularly important. Under the high temperature conditions inside the battery, pure copper is easily oxidized. Therefore, in subsequent scientific research, it is also particularly important to optimize the passivation solution with more significant passivation effect. The most ideal effect is to be able to maintain its original appearance under the shortest immersion time and high-temperature baking time. It is also a difficult problem that scientific researchers who produce copper foil need to continue to solve.

[0045] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for producing ultra-thin high tensile strength and high elongation copper foil, characterized in that: The following steps are involved: (1) Distilled water, copper sulfate pentahydrate, and concentrated sulfuric acid are used to prepare a basic electrolyte, wherein the basic electrolyte contains Cu 2+ Concentration is 80 85 g / L, H2SO4 concentration is 111 130 g / L; Pour the electrolyte into the electrolytic cell and heat it to the working temperature 40 65℃; (2) adding chloride ions, leveling agents, brighteners, inhibitors, and sulfur-containing additives into the electrolytic cell; The chloride ion is hydrochloric acid or hydrochloride, and the chloride ion concentration is 28 34 mg / L; The leveling agent is one or more of gelatin, collagen or quaternary ammonium salt compounds containing conjugated bonds, and its concentration is 8 25 mg / L, any ratio when mixed; The brightener is one or more of ethylene thiourea, sodium 3-mercapto-1-propane sulfonate, and sodium polydisulfide propane sulfonate, with a concentration of 3.0 13 mg / L, any ratio when mixed; The inhibitor is one or more of polyethylene glycol, polypropylene glycol, and polyoxyethylene ether, with a concentration of 2.0 23mg / L, any ratio when mixed; The sulfur-containing additive is one or more of sodium thiazoline dithiopropane sulfonate, 4-phenylimidazole, tetrahydrothiazolidinethione, 5-methylthiazole and 2-mercaptobenzimidazole, with a concentration of 0.5 21 mg / L, any ratio when mixed; (3) Turn on the DC power supply and set the current density to 30 60 A / dm 2 , power-on time is 200 500 s; (4) After electroplating, remove the cathode plate, rinse it with a large amount of distilled water, and then immerse it in the passivation solution for 5 minutes. 300s, take it out and rinse it again with a large amount of distilled water to rinse out the residual solution and passivation solution and then dry it; (5) After drying, the copper foil is peeled off from the cathode plate to obtain a bright copper foil. The ultra-thin high tensile strength and high elongation copper foil has the following performance parameters: Copper foil thickness is 4μm 12μm, elongation 10.60% 19.80%, roughness Ra of matte surface is 0.04μm 0.46μm, Rz is 0.66μm 1.63μm, tensile strength 650 MPa 950 MPa.

2. The method for producing an ultra-thin high tensile strength and high elongation copper foil according to claim 1, characterized in that: The chloride ions in step (2) are provided by hydrochloric acid; the hydrochloride is sodium chloride or potassium chloride.

3. The method for producing an ultra-thin high tensile strength and high elongation copper foil according to claim 1, characterized in that: Turn on the DC power supply as described in step (3) and set the current density to 35 A / dm 2 , the power-on time is 300s.

4. The method for producing an ultra-thin high tensile strength and high elongation copper foil according to claim 1, characterized in that: The passivation solution described in step (4) is obtained by stirring and evenly mixing 21.0 g of citric acid, 2 mL of phytic acid mother liquor, 0.5 g of sodium tungstate, 0.1 g of benzotriazole and 1.0 mL of lactic acid, adding them to 100 mL of distilled water to dissolve them, and adjusting the pH value to make it slightly acidic.

5. An ultra-thin high tensile strength and high elongation copper foil, characterized in that: The method for producing an ultra-thin high tensile strength and high elongation copper foil according to any one of claims 1 to 5 is used to obtain the ultra-thin high tensile strength and high elongation copper foil having the following performance parameters: the copper foil thickness is 4 μm 12μm, elongation 10.60% 19.80%, roughness Ra of matte surface is 0.04μm 0.46μm, Rz is 0.66μm 1.63μm, tensile strength 650 MPa 950 MPa.

Citation Information

Cited By

  • Additive of 1-micron electrolytic copper foil and preparation method of 1-micron electrolytic copper foil

    CN121915467A

  • Additive for 1-micron electrolytic copper foil and method for producing 1-micron electrolytic copper foil

    CN121915467B